Pengembangan kegiatan proyek penguatan profil pelajar Pancasila (P5) berorientasi moderasi beragama - Nashihin, M. Ihsan; Kamaludin, Faisal Sundani; Ulum, Bahrul (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
The purpose of the study was to explain the process of developing learning strategies in the Pancasila Student Profile Strengthening Project (P5) activities to improve the quality of religious moderation in students in schools. The development process was carried out based on scientific studies, expert opinions and scientific methodology steps. The study used a development method with four steps, analyzing activities, developing P5 based on scientific studies and expert opinions, conducting trials and dissemination in schools. The results of the study found that the improvement in quality was good. The value of religious moderation was 88.53, where the previous year was only 81.38. National commitment scored 88.25 where previously it was 80.60, tolerance scored 90.01 which was previously 82.28, anti-violence scored 88.03 where previously it was 76.92 and finally 90.12 where previously it was 85.73. This study contributes to providing ideas for policy makers and teachers that improving the quality of religious moderation in schools can be done with concrete, planned and measurable steps through the development of P5 learning strategies in the classroom. Keywords: Learning Strategy, Religious Moderation, Tolerance, Diversity, Pancasila Student Profile Strengthening Project (P5).